Passage to India: Oscillating between love and hate. The emotional reception of India as the subject of Indian studies - Mickevičienė, Diana (Acta Orientalia Vilnensia, 2008)
Vilnius UniversitySince time immemorial, India has evoked strong emotional reactions from the Europeans attracted by her rich civilisation. These reactions range from love beyond explanation to shock and panic leaving a deep impact on the personality concerned. In this presentation, the author touches upon the problem of the emotional reactions to India among the European general public and its possible written sources. One can often notice that even the scholars of Indian studies succumb to certain emotional biases that breed different sorts of stereotypes about India. This article therefore argues that it is necessary to reflect academically upon these extreme emotional interpretations of India, both those of Indologists and of common people.